Treatment of leprosy-induced plantar ulcers - Katia Torres Batista; Gabriela Bernarda Monteiro; Ulises Prieto Y-Schwartzman; Ana Flavia Saraiva De Sa Aureliano Roberti; Adelaine Gomes Rosa; Carolina Zampronha Correia; Camila Freire Parente Alves da Silva (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Leprosy-induced plantar ulcers result from a lack of plantar sensitivity. Objective: This study aimed to describe the treatment provided to patients with leprosy-induced plantar ulcers. Methods: We retrospectively reviewed the medical records of patients with plantar ulcers treated at Sarah Hospital in Brasilia from 2006 to 2016 and collected information about sex, age, etiology, location, and treatment. Results: A total of 27 patients (17 [62.96%] men, 10 [37.04%] women; 40.74% were aged 41-60 years) were treated from Goiás and the Federal District. All required ≥1 surgical procedure. Conclusion: A higher frequency of advanced grade was observed in men, primarily on the first toe. All needed surgical and non-surgical procedures and achieved complete wound healing. Transtibial amputation was required in 1 case and toe amputation in 7 cases; 90% patients developed ulcer recurrence after 1 year.